A mobilização do conhecimento científico por egressos de um mestrado em Enfermagem sob o olhar da análise institucional - Depes, Valéria Binato Santili (2013)
This study has as its central theme the education and knowledge production in nursing level in the strict sense, and objectives: understand how the formation process in a academic master has contributed to the mobilization of scientific knowledge, by graduates of master's nurses who are working in the world of nursing care, in reality limited; and apprehend the constant tensions and difficulties settling in the working world, facilitating and/or hindering the graduates of master's nurses, the management and utilization of such knowledge by proposing new ways of qualifying care spaces, in health services and nursing, from the theoretical perspective of Institutional Analysis. One of the presupposed of the study is that the formation process in academic master, the supply of new scientific knowledge and diverse educational experiences, contributes to new and alternative ways to perform the services, that deserve to be known by the survey. The other presupposed from which we start is that there are many difficulties and tensions in the process of management, use, and also to implement new scientific knowledge, in the daily realities of nursing care, that transcend the desire for change that may have been aroused the process of knowing in the Masters. As a method, we chose exploratory qualitative approach; were 09 subjects in the study, from 2008 to 2011 graduates of the Master of Nursing. As inclusion criterion, should act in the processes of care or managing nursing care. As a technique for data collection used the semi-structured interview; for the organization and analysis, we chose the thematic analysis. As a result, we got four thematic analysis, which were: a) The master's degree as device the institution's knowledge; b) Aspects instituting and instituted the use of different forms of knowledge by graduates of the Masters; c) Masters and teaching as activities that encourage and nurture the institution's knowledge; d) The exploration, domination and mystification as deformations of the Social Utopia. The Institutional Analysis, as a theoretical, proved capable of giving meaning to the findings of field, helping to interpret and appreciate the uniqueness of each subject in the mobilization of scientific knowledge. Thus, it was found that the Masters through the educational process, acted like device that animated the institution knowledge and caused changes in the singular realities of nursing services; research, instrument of knowledge, encouraged the graduates the tools necessary to constant updating scientific and act for a critical, reflective and ethical. It was identified in establishments where subjects act, the presence of vicious situations (exploration/domination/mystification) and 'reverse dialectic' between instituted/instituting, organized/organizing which tend to undermine and hamper the potential instituting of the subject, provided by Master’s degree. The subjects of the study say the masters prepared them for have a better understanding of limits and possibilities and to extend their ability to reason and intervene in the working world. Believe make better political management of scientific knowledge, contributing to the emergence of new institutional arrangements through their instituting movements, strengthening the science of nursing in a specific location.